2019
DOI: 10.1111/ppc.12354
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of work‐related fatigue among Jordanian emergency department nurses

Abstract: Purpose This study purposed to assess the psychosocial correlates of work‐related fatigue among Jordanian emergency department nurses. Design and Methods A cross‐sectional study was conducted among Jordanian emergency nurses (n = 220). Measures included Occupational Fatigue Exhaustion/Recovery Scale (OFER15) and Copenhagen Psychosocial Questionnaire version Two (COPSOQ II). Findings The psychosocial factors correlated with all types of work‐related fatigue (acute, chronic, and inter‐shift [recovery]) were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
3
14
0
7
Order By: Relevance
“…The shift work of health workers aggravates fatigue and musculoskeletal problems (24,40) . Work shifts also interfere with family life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift work of health workers aggravates fatigue and musculoskeletal problems (24,40) . Work shifts also interfere with family life.…”
Section: Discussionmentioning
confidence: 99%
“…Home care workers have less quantitative and emotional demands, less work conflict, privacy and better development possibilities. 14 Ismail et al (24) 2019 Jordan…”
mentioning
confidence: 99%
“…Studies found that 91.9% of nurses complained of work-related fatigue with a higher level among female nurses [23]. Concerning fatigue, the study revealed that in an eight hour shift system there were no significant differences in fatigue (chronic fatigue, acute fatigue, and inter-shift [recovery]) between the three types of rotations as measured by the Occupational Fatigue Exhaustion/Recovery Scale, but the study had a lower average score than other studies [22]. The result is supported by previous studies which showed no significant relationship between the number of night-shifts and fatigue [24,25].…”
Section: Discussionmentioning
confidence: 57%
“…Work-related fatigue is one of the most common phenomena among shift workers, particularly nurses [22]. Studies found that 91.9% of nurses complained of work-related fatigue with a higher level among female nurses [23].…”
Section: Discussionmentioning
confidence: 99%
“…Workplace sexual harassment can adversely affect workers ‘psychophysical well-being[19], their motivation, safety, satisfaction, productivity and the efficiency of the whole health organization[20]. It can also impact on patients’ safety, since any aspect related to the assistance, care or treatment necessary for the patient might be omitted, delayed or left unfinished because of the sexual harassment[21-22].…”
Section: Introductionmentioning
confidence: 99%